Analysis of the Implementation of Good Corporate Governance Principles in Risk Management at Islamic Bank PT. BPRS Puduarta Insani - Della, Della Alvionita; Nasution, Juliana; Yanti, Nursantri (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study uses a qualitative approach with data collection methods, namely observation, interviews and documentation. The analysis process in this study is data reduction, description, drawing conclusions and finally checking the validity of the data. Based on the results of the research and analysis conducted by the author, it can be concluded that the implementation of good corporate governance (GCG principles) in the management of financing risks at BPRS Puduarta Insani has been implemented well. There are five aspects of the principles of Good Corporate Governance (GCG) that have been implemented well, namely transparency, accountability, responsibility, independence, and fairness. The implementation of GCG in managing risk management at PT. BPRS Puduarta Insani shows that the company has implemented these principles well. This bank has also developed a risk management strategy to manage its operational activities effectively and maintain optimal performance. However, BPRS Puduarta Insani is currently facing challenges, such as customers who experience delays in paying bills, or what is often referred to as bad debt.